A modular approach to multifunctional polypeptide/ceramic fluorapatite‐based self‐assembled system in affinity chromatography for the purification of human Immunoglobulin G1. Issue 3 (9th February 2015) - Islam, Tuhidul; Fernández‐Lahore, Marcelo; Fleminger, Gideon; Jungbauer, Alois
<x xml:space="preserve">Abstract</x> The multifunctional bone sialoprotein/apatite (AP) self‐assembled systems in the mineralized tissues show a pathway for the noncovalent immobilization of ligands on the AP chromatographic matrix. A model approach is presented here regarding the physical immobilization of ligands on the ceramic fluorapatite (CFT) matrix for the purification of human Immunoglobulin G (hIgG). The peptide pIC, HWRGWV–KPRSVSG, composed of a hIgG‐specific peptide, HWRGWV (pLI), and a CFT‐specific peptide, KPRSVSG (pTC), was synthesized and subjected to physicochemical characterization. A circular dichroism study showed that pIC possesses a flexible structural feature, which is significant in terms of its multifunctional activities. With the current approach, hIgG will be retained selectively by the self‐assembled pIC/CFT column, while other biomolecules will pass through the column without being interacted. Therefore, the chromatographic conditions that are the key factors for the successful implementation of this technique were optimized as a function of the composition and pH of the mobile phase. Here, 115 mM sodium chloride (NaCl) in 20 mM sodium phosphate, pH 7.4, was used as the binding buffer, and the elution was performed with 225 mM NaCl in 20 mM sodium phosphate containing 0.3% w/v sodium acetate at pH 6. The binding capacity of the pIC/CFT column was 21.5 mg hIgG/ml matrix with a ligand density of 18.8 µmol/ml, and the binding capacity of the column increased with the increment of ligand density. Afterward, the applicability of a spacer arm between pLI and pTC was also verified. The hIgG‐binding capacity of the column decreased with the increment in size of the spacer. In conclusion, the peptide‐mediated self‐assembled biomimetic system can be used as an alternative to the chemical immobilization of ligands in order to prevent unwanted consequences that result from some of the conventional ligand coupling chemistry. Copyright © 2015 John Wiley & Sons, Ltd.